Efeito toxicológico do extrato seco de Tribulus terrestris L. em ratos wistar - Lopes, Edimara Machado (2018)
The search for the perfect body, with the objective of immediate evolution in performance or aesthetic purposes, is increasingly evidenced by the media. With this, the use of anabolic steroids androgens, such as synthetic derivatives of testosterone and medicinal plants with corresponding action, is increasing. In the context of the plants used for these purposes, the extract of Tribulus terrestris L. (TT), also known as puncture vine or malt cross, is the most popular. This belongs to the family Zygophylaceae and has its origin in India. Some studies attribute antifungal, hypoglycemic and aphrodisiac properties, also presenting a therapeutic potential in the treatment of cardiocirculatory and depressive conditions. In addition, it is popularly used because of its relationship to the modulation of testosterone levels. Therefore, it is of great importance to investigate the toxic effects of the agents used for the purpose of increasing physical performance, since the indiscriminate consumption of these substances can cause damage to the body. Thus, the objective of this study was to investigate the acute oral toxicity and repeated doses of the dry extract of TT, in order to analyze the safety character of this plant. In acute toxicity, a single dose of 5000 mg / kg TT was administered (orally-gavaged) in female Wistar rats and the observations on behavioral changes and signs of toxicity were followed for 14 days. In the repeated dose study, TT was administered (gavage) daily for 28 days in male and female Wistar rats at doses of 500, 750 and 1000mg / kg. Control groups received distilled water in both studies. During the study period, body weight was recorded daily. At the end of 14 (acute) and 28 (repeated doses) days euthanasia was performed, followed by biochemical and enzymatic evaluations (CAT, SOD and TBARS) and histological analyzes. In the acute study, the dose of 5000 mg / kg did not induce mortality, and TT was classified as safe. However, for the treatment of repeated doses significant changes were observed in some biochemical, histological, CAT, SOD and TBARS parameters for all doses administered and in both sexes. Being that the damage was more expressive in males. These results indicate that single dose exposure does not induce toxicity to animals. However, repeated dose administration may be primarily harmful to the liver.